Effect of Deposition Angle on Diamond-like Carbon Films on Silicon Trenches: A Molecular Dynamics Study - Acero, Alejandro Joaquin A. (Archīum Ateneo, 2025)
Known for its exceptional mechanical properties, diamond-like carbon (DLC) serves as an effective coating capable of improving a material’s performance in a variety of applications. While difficult to produce and analyze experimentally, molecular dynamics simulations serve as a sufficient method by which a material such as DLC can be studied at an atomistic level with respect to its microstructural properties. Large-scale atomic/molecular massively parallel simulator was used for the simulation while open visualization tool was used for visualization. In this study, C atoms were deposited onto Si trenches of multiple aspect ratios (0, 0.25, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, and 3.5) at varying deposition angles (0°, 15°, 30°, and 45°). Tersoff potential was used to define the interactions between Si–Si, Si–C, and C–C atoms. The effectiveness of the coating was assessed by inspecting the thickness conformity along the sidewall and bottom surfaces along with the sticking coefficients and radial distribution functions (RDF) of the deposited carbon films. At low deposition angles, the trench bottom was better coated whereas at higher deposition angles rougher films were obtained and thicker sidewall films were observed. RDF graphs showed similar results to DLC as observed in the literature. At higher aspect ratios of 2.0 and greater, deposition at low angles did not sufficiently coat the sidewalls whereas the shadowing effect prevented deposition at higher angles onto the lower portion of trench structures. The findings of this study contribute to the discussion regarding three-dimensional coating techniques for DLC which has applications in medical implants. Simulation of more C deposition onto trenches of higher aspect ratio is recommended to determine the extent of the shadowing effect and identify if sufficient coating is indeed possible (Figure Presented).